2021
DOI: 10.1007/s10389-021-01481-6
|View full text |Cite
|
Sign up to set email alerts
|

Polish students’ knowledge of dietary supplements

Abstract: Background The increasing intake of dietary supplements (DS) can be observed worldwide. These preparations are classified as a special category of foods and are subject to food law, not pharmaceutical regulations. As a result, the requirements for DS are much less restrictive than for medications. Methodology This research was conducted in a group of young Polish students of pharmacy at the Medical University of Silesia in Katowice (SUM) and of finance and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
1
0
0
Order By: Relevance
“…In the present study, the greatest differences in the prevalence of other DS use were observed between the Polish and English Divisions. Among English Division students, 38% declared the use of other DS or OTC drugs, which is consistent with results from other countries [ 50 , 53 ], but in the Polish Division, 68% of students took DS, which is more similar to the data obtained by Miljković et al [ 38 ] or in a study by Brodziak et al [ 54 ]. It is, however, worth mentioning that many studies were performed before the COVID-19 pandemic.…”
Section: Discussionsupporting
confidence: 89%
“…In the present study, the greatest differences in the prevalence of other DS use were observed between the Polish and English Divisions. Among English Division students, 38% declared the use of other DS or OTC drugs, which is consistent with results from other countries [ 50 , 53 ], but in the Polish Division, 68% of students took DS, which is more similar to the data obtained by Miljković et al [ 38 ] or in a study by Brodziak et al [ 54 ]. It is, however, worth mentioning that many studies were performed before the COVID-19 pandemic.…”
Section: Discussionsupporting
confidence: 89%